Answer:
572.5
Step-by-step explanation:
A=6ah + 3√(3) a²= 6·8·5+3√(3)·8²≈572.55376
a is base length and h is height
Answer:
y(-4) = 5
y'(-4) = -7
Step-by-step explanation:
Hi!
Since the tangent line T and the curve y must coincide at x=-4
y(-4) = T(-4) = 5
On the other hand, the derivative of the curve evaluated at -4 y'(x=-4) must be the slope of the tangent line. Which inspecting the tangent line T(x) is -7
That is:
y'(-4) = -7
Answer:
105
Step-by-step explanation:
Given : a = 3, b = 12
3 ⁴ = 81
2 x 12 = 24
Result:
81 + 24
= 105